ArcGIS for Environmental and Water Issues - Bajjali, William (Springer, 2018)
The study of geographic information systems (GIS) applications is enlightening, challenging, and very interesting. This workbook was created as a guide to students and professionals on the applications of GIS in the geoscience field. GIS applications is now considered an important course in the curriculum of undergraduate geoscience, environmental, and in some fields of engineering programs. It is a result of several years of experience in applying GIS technology to water resources and environment related problems. The databases and the applications used in the text reflect real world problems from different environmental settings that have been gathered from the author’s works in the USA and the Middle-East. Each chapter presents a different set of scenarios and case studies that include an environmental problem that needs a solution. A step-by-step approach was adopted to provide answers and solutions to the problems for the scenarios presented. The textbook is intended as an introductory course either at the undergraduate level or as a dual-level undergraduate/graduate course, and it can be used as a self-study workbook for professionals in the field of geoscience. It aims to teach students and professionals the various environmental disciplines of mapping and spatial analysis skills using ArcGIS and state of the art methodologies to acquire, visualize, and analyze data.